Covid-19 created a gender gap in perceived work productivity and job satisfaction: implications for dual-career parents working from home - Feng, Zhiyu; Savani, Krishna (Gender in management, 2020)
Purpose This paper aims to examine gender gaps in work-related outcomes in the context of Covid-19. The authors hypothesized that the Covid-19 pandemic would create a gender gap in perceived work productivity and job satisfaction. This is because when couples are working from home the whole day and when schools are closed, women are expected to devote more time to housework and childcare. Design/methodology/approach The authors used a sample of employed women and men from dual-career families who were working from home since Covid-19 lockdowns started. In total, 286 US-resident full-time employees participated in this study. Participants were asked to report their work productivity and job satisfaction before and since Covid-19 lockdowns. Findings It is found that before the Covid-19 pandemic, there were no gender differences in self-rated work productivity and job satisfaction. However, during the lockdown, women reported lower work productivity and job satisfaction than men. Research limitations/implications Participants retrospectively reported their work productivity and job satisfaction before Covid-19. However, there are unlikely to be systematic gender differences in retrospective reports of these measures. Further, the authors only sampled opposite-sex dual career parents. Future research needs to examine the effects of lockdowns on women and men in other types of households. Practical implications Given the nature of the Covid-19 pandemic, many regions might experience multiple periods of lockdown, and many workplaces have already adopted or are likely to adopt long-term work-from-home policies. The findings indicate that these long-term changes in the workplace might have long-term negative effects on women’s perceived productivity and job-satisfaction in dual-career families. Social implications The findings suggest that society needs provide additional support to women working from home and taking care of children or other dependents, particularly during lockdowns or during times when schools and daycare centers are closed. Originality/value The current research is one of the first to claim that despite the greater amount of time that women spend in housework and childcare than men, during normal times, they are as productive and as satisfied with their job as men. However, the Covid-19 pandemic increased women’s housework and childcare beyond a threshold, thereby creating a gender gap in work productivity and job satisfaction.